Effect of alkali-activated metakaolin cement on compressive strength of mortars - Wianglor K. (2017)
© 2017 Elsevier B.V. This paper reports the compressive strength and microstructure characteristic of alkali-activated metakaolin (MK) cement under two curing methods. MK was used to replace part of Portland cement (PC) at 70, 80, 85, 90, 95 and 100% by mass of binder. Sodium hydroxide (NaOH) and sodium silicate (Na 2 SiO 3 ) were used as activating agents (Na 2 SiO 3 to NaOH ratio of 0.67). NaOH with 10 molar concentrations, liquid alkali/binder ratio of 0.8 and water base was used. Mortar and paste specimens were cured at 23 ± 2°C (55% RH) and 60°C (95% RH). The results indicated that calcium silicate hydrate (C–S–H) and calcium carbonate (CaCO 3 ) phases were detected by thermogravimetry (TGA). Setting time and drying shrinkage decreased when metakaolin replacement level increased, the compressive strength of alkali-activated metakaolin cement increased with the increase of PC content and increased with temperature. The curing of specimens at 60°C (95% RH) enhanced the compressive strength, matrices appeared denser than when cured at 23 ± 2°C (55% RH) and phases of (C, N)-A-S-H gel and or C–S–H gel can be seen clearly.